(untitled) (Bangladesh Critical Care Journal, 2014)
In this part of world, the mode of presentation of type 2 diabetes is enormously varied and infections may be the first presenting feature of previously unknown diabetes. In this case, we report an initial way of presentation of type 2 diabetes mellitus as emphysematous pyelonephritis. He was treated successfully by antibiotics and percutaneous drainage. Emphysematous pyelonephritis is a rare life-threatening gas-producing, necrotizing infection of the renal parenchyma and surrounding areas which can be focal or diffuse and may spread to the collecting system or perinephric tissues. It is rapidly progressive and fatal if untreated. Prompt recognition and aggressive treatment helps in complete recovery of patients. DOI: http://dx.doi.org/10.3329/bccj.v2i1.19971 Bangladesh Crit Care J March 2014; 2 (1): 46-47